Correlation between the use of albumin infusion and concentrations of serum albumin, proinflammatory cytokines (tnf-ï¡, il6) and sofa score in septic patients - Utariani, Arie; Prasetyo, Budi; Nugraha, Jusak (Folia Medica Indonesiana, 2017)
Sepsis is a major problem causing high morbidity and mortality in patients who hospitalized in intensive care. In sepsis, there is a change in the distribution of albumin in the intravascular and extravascular compartment, so hipoalbumin is occured. Using albumin in septic patients from several studies that have been done are still controversial. Analyzing albumin infusion with changes in levels of albumin, cytokines and SOFA score in septic patients in intensive care dr. Soetomo. The design of this study is a prospective longitudinal observational. The study was conducted in the intensive care unit or ICU dr. Soetomo in February 2015. The inclusion and exclusion criteria were determined that obtained 15 research subjects. They were examined with serum albumin and proinflammatory cytokines as well as evaluating the SOFA score. Then, it measure with ANOVA test methods. Infusion of albumin positively correlated with increased levels of serum albumin and a negative correlation with the levels of IL6, TNF-a and SOFA score. It also found a correlation between changes in levels of albumin with changing levels of IL6 (p <0:01) and changes in SOFA score (p <0.05).